High-corrosion-resistance and high-strength zinc-aluminum-magnesium coated steel plate and manufacturing method thereof
By using low Si and low Mn substrates and optimizing zinc and aluminum magnesium plating solutions in zinc-aluminum magnesium plating, the problem of insufficient corrosion resistance of zinc-aluminum magnesium plating in strict environments is solved, and high strength and high resistance are achieved Corrosiveness and avoids poor adhesion problems in traditional methods.
Patent Information
- Application Number
- CN202411355070.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-09-27
AI Technical Summary
The existing zinc-aluminum-magnesium plating is insufficient in harsh environments, and the cost and process complexity increase when traditional methods increase strength, resulting in poor adhesion of the coating.
Using low Si and low Mn substrates, the zinc-aluminum magnesium plating solution composition and manufacturing process are adjusted, including low-temperature annealing, radiation tube heating, pickling cold rolling and hot dip plating, forming zinc-aluminum magnesium plating with high yield strength and tensile strength , avoid the use of enhanced elements such as Nb and Ti.
It realizes high strength and corrosion resistance of the steel plate without adding alloy elements, ensures good adhesion of the coating, and reduces production costs and process complexity.
Smart Images

Figure CN119243048A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hot-dip galvanized aluminum-magnesium steel materials, and specifically relates to a high-corrosion-resistant and high-strength zinc-aluminum-magnesium coated steel plate and a manufacturing method thereof. Background Art
[0002] Zinc-aluminum-magnesium coating is a new coating that adds a certain amount of Al and Mg to the traditional zinc-based coating. The corrosion resistance is 3 to 5 times higher than that of pure zinc coating products. It is widely used in industries such as construction, photovoltaic brackets, and highway guardrails. At present, the Al content of "China Aluminum" zinc-aluminum-magnesium coating products that are widely used in the market does not exceed 11%, and the Mg content does not exceed 3%. For the demand for materials in relatively harsh environments, such as materials for construction facilities in coastal areas or high humidity and high temperature areas, the corrosion resistance of coating products needs to be further improved.
[0003] In addition, the idea of high-strength thinning can be used in industries such as construction materials. By replacing ordinary steel plates with high-strength steel plates with a yield strength of 500MPa or more and reasonable structural design, the amount of steel used can be reduced without reducing safety. However, for the production of steel plates above 500MPa, the traditional steel plate alloy composition usually increases the Si and Mn content, and adds elements such as Nb and Ti, and uses precipitation strengthening and phase transformation strengthening to improve strength. This method not only increases the alloy cost and process cost, but also the increase in the alloy element content brings difficulties to the hot-dip production process. For example, the enrichment of alloy elements on the surface of the coating will cause leakage plating, poor adhesion of the coating, and other problems. Therefore, taking into account both high corrosion resistance and high strength is a technical difficulty faced. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a high corrosion-resistant and high-strength zinc-aluminum-magnesium coated steel plate and a manufacturing method thereof in view of the deficiencies in the prior art, which achieves high strength and high corrosion resistance under the condition of low Si and low Mn content in the substrate and without adding strengthening elements such as Nb and Ti.
[0005] In order to solve the technical problem proposed by the present invention, the present invention provides a high corrosion resistance and high strength zinc-aluminum-magnesium coated steel plate, including a substrate and a zinc-aluminum-magnesium coating formed by a hot-dip zinc-aluminum-magnesium plating solution.
[0006] In the above scheme, the chemical composition and mass percentage of the substrate are: C: 0.02-0.07%, Si: 0.02-0.10%, Mn: 0.7-0.9%, Als: 0.02-0.07%, P≤0.025%, S≤0.02%, and the remainder is Fe and other inevitable impurities.
[0007] In the above scheme, the chemical composition and mass percentage of the zinc-aluminum-magnesium plating solution are: Al: 30.0-45.0%, Mg: 5.0-8.0%, Si: 0.5-1.2%, and the remainder is Zn and other inevitable impurities.
[0008] In the above scheme, the yield strength of the high corrosion-resistant and high-strength zinc-aluminum-magnesium coated steel plate is ≥550MPa, the tensile strength is ≥550MPa, and the elongation is ≥4%.
[0009] The present invention also provides a method for manufacturing a high-corrosion-resistant and high-strength zinc-aluminum-magnesium coated steel plate, comprising the following steps:
[0010] 1) Smelting and continuous casting
[0011] Continuous casting after smelting according to the composition of the substrate;
[0012] 2) Hot rolling
[0013] The continuously cast slab is heated and then hot rolled;
[0014] 3) Pickling and cold rolling
[0015] The obtained hot-rolled coil is pickled and then cold-rolled;
[0016] 4) Hot dip galvanizing
[0017] The cold-rolled substrate is heated to the annealing temperature in an annealing furnace using a radiation tube for heat preservation, and then put into a zinc pot for hot-dip zinc-magnesium-aluminum plating solution, and then cooled out of the pot to obtain a high-corrosion-resistant and high-strength zinc-aluminum-magnesium coated steel plate.
[0018] In the above scheme, the furnace exit temperature of the heated slab is 1150-1190°C.
[0019] In the above scheme, the final rolling temperature of the hot rolling is 800-840°C.
[0020] In the above scheme, the hot-rolled strip is cooled to 520-570°C and then coiled.
[0021] In the above scheme, the temperature of the acid solution for pickling is 85-90°C.
[0022] In the above scheme, the total reduction ratio of the cold rolling is 50-70%.
[0023] In the above solution, the thickness of the substrate is 0.40 to 2.5 mm.
[0024] In the above scheme, the heating rate of the radiation tube heating is 5 to 30 K / s.
[0025] In the above scheme, the annealing temperature is 570-590° C., and the holding time is 40-80 seconds.
[0026] Furthermore, the annealing temperature and the holding time satisfy the formula: t=1220-2×T; wherein T is the annealing temperature, in units of °C; and t is the holding time, in units of seconds.
[0027] In the above scheme, the hydrogen concentration in the annealing furnace is ≥15%, and the dew point is ≤-40°C.
[0028] In the above scheme, the microstructure of the substrate after annealing includes ferrite and carbide, wherein the area of the deformed non-recrystallized microstructure accounts for 85-96%.
[0029] In the above scheme, the plate temperature of the substrate when entering the zinc pot is 5 to 10° C. higher than the temperature of the zinc-magnesium-aluminum plating solution.
[0030] In the above scheme, the temperature of the zinc-magnesium-aluminum plating solution is 30-40° C. higher than its melting point.
[0031] In the above scheme, the average cooling rate of the cooling after taking out of the pot is greater than 35K / s.
[0032] In the above scheme, the thickness of the zinc-aluminum-magnesium coating on one side is 30-350 g / m 2 .
[0033] In the above solution, the zinc-aluminum-magnesium coating includes a coating layer and an interface layer between the substrate and the coating layer.
[0034] Furthermore, the structure of the coating layer includes a primary crystal (Al) phase, a MgZn2 phase, a multi-element eutectic Al / Zn / MgZn2 structure, and a Mg2Si phase.
[0035] Furthermore, the interface layer is a dense Al-Fe compound containing a small amount of Si.
[0036] The design concept of the present invention on the chemical composition of the substrate is as follows:
[0037] Since the high strength of the steel of the present invention mainly comes from the large amount of deformed non-recrystallized structures retained in the substrate after low-temperature annealing, the selection of alloy elements for the substrate can adopt a low Si and low Mn composition design, and no strengthening elements such as Nb and Ti are added. The content of the main alloy elements is controlled as follows:
[0038] C: Carbon exists in two forms, solid solution in ferrite and forming carbides to improve the strength of steel. Conventional hot rolled coils or CSP hot rolled coils can be used in the cold rolling process of the present invention. The peritectic region should be avoided in the CSP hot rolling process, and the improvement of material strength mainly comes from the cold rolling deformation structure. Therefore, the present invention controls the C content to 0.02-0.07%.
[0039] Si: Silicon is an important reducing agent and deoxidizer in the steelmaking process. Si does not form carbides, but is dissolved in ferrite to increase the strength of ferrite. However, when the Si content is high, when heated in an oxidizing atmosphere, the Si on the surface of the steel is prone to form oxides with O, reducing the wetting of the plating solution on the steel base surface, thereby causing defects such as exposed plating or poor coating adhesion. Since the improvement in the strength of the steel of the present invention mainly comes from the cold-rolled deformation structure, the Si content can be controlled at a lower level. The present invention controls the Si content to 0.02-0.10%.
[0040] Mn: Manganese is an excellent deoxidizer and desulfurizer in steelmaking. Mn is dissolved in ferrite to improve the strength of ferrite. However, when the Mn content is high, when heated in an oxidizing atmosphere, the Mn on the surface of the steel is easy to form oxides with O, reducing the wetting of the plating solution on the steel base surface, thereby causing defects such as exposed plating or poor coating adhesion. Since the improvement in the strength of the steel of the present invention mainly comes from the cold-rolled deformation structure, the Mn content can be controlled at a lower level. Therefore, the present invention controls the Mn content to 0.7-0.9%.
[0041] The design concept of the present invention on the chemical composition of the zinc-aluminum-magnesium plating solution is as follows:
[0042] Al: The aluminum content is increased, and the corrosion resistance of the coating is improved. Since the present invention adopts low-temperature annealing, the low-temperature heating has a weak cleaning effect on the surface of the substrate. The cleanliness of the surface of the steel strip before entering the zinc pot is not as good as that of the steel strip heated at high temperature. For example, there may be a small amount of fine iron oxide scale residue or local oxidation, etc. The reactivity of the steel strip and the plating solution will be reduced. Therefore, it is easy to produce defects such as missed plating or poor adhesion during the hot plating process. Since the reaction between Al and Fe is very intense, the formation of the Al-Fe interface layer on the substrate can be promoted by increasing the Al content in the plating solution and increasing the corrosion of the plating solution on the steel plate, thereby reducing the incidence of defects such as missed plating or poor adhesion. When the Al content is less than 30%, it is not easy to form a continuous Al-Fe interface layer on the substrate when there is local oxidation on the surface of the steel strip, thereby producing defects such as missed plating or poor adhesion. When the Al content is greater than 45%, the melting point of the plating solution increases, and the plating solution temperature will exceed the production temperature of the substrate, and the hot plating process will reduce the strength of the substrate. In addition, the increase in the Al content will produce more zinc slag, affecting the plating process. Therefore, the Al content in the coating is controlled to be 30-45%.
[0043] Mg: As the magnesium content increases, the corrosion resistance of the coating improves, and the effect of Mg on improving corrosion resistance is greater than that of Al. The corrosion products of Zn, Al and Mg are fluid and can effectively protect the incision. However, since Mg is an easily oxidized element, an increase in the Mg content will lead to an increase in slag during the production process. At the same time, an increase in the Mg content will lead to a significant increase in the massive MgZn2 phase, and these hard and brittle MgZn2 are prone to cracking during processing. Therefore, the present invention controls the Mg content in the coating to 5.0-8.0%.
[0044] Si: The present invention improves the reaction between the plating solution and the substrate by a higher Al content, and promotes the formation of the Al-Fe interface layer on the substrate. However, the Al-Fe interface layer should not grow excessively. In order to prevent the interface layer from being too thick, the Si content is controlled at 0.5-1.2%. Too low Si content cannot effectively inhibit the growth of the Al-Fe interface layer, and the plating solution will seriously corrode the steel base. Too high Si content will form too many brittle compounds containing Si on the interface layer of the substrate, thereby reducing the machinability of the coating.
[0045] The design concept of the present invention in the manufacturing method is as follows:
[0046] In order to ensure that a large amount of deformed and unrecrystallized structures are retained in the structure after hot-dip galvanizing to ensure high strength, the temperature must be below the recrystallization temperature during the annealing process before hot-dip galvanizing to prevent most of the substrate structure from recrystallizing and causing a significant drop in strength. However, due to the low heating temperature, the heating process has a weak cleaning effect on the strip surface. Therefore, in order to ensure the surface quality and adhesion of the coating, it is particularly important to control the iron oxide scale on the substrate surface before the hot-dip process. The main process points are as follows:
[0047] Casting billet out of furnace temperature: Too high a furnace out temperature will cause the casting billet to form too thick iron oxide scale on its surface during the heating process. The present invention sets the furnace out temperature to 1150-1190°C.
[0048] Final rolling temperature: secondary iron scale will be generated on the surface of the steel coil during the cooling process after rolling. Too high a temperature will result in more secondary iron scale being generated during cooling. The final rolling temperature is set to 800-840°C in the present invention.
[0049] Coiling temperature: During the air cooling process after coiling, tertiary scale will be generated on the surface of the steel coil. Too high a coiling temperature will result in more tertiary scale being generated during air cooling, while too low a temperature may cause the coil head to tilt during the coiling process, thereby affecting the coiling. The present invention sets the coiling temperature to 520-570°C.
[0050] Pickling temperature: During the pickling process, the iron oxide scale on the surface of the strip will be dissolved and removed. If the acid solution temperature is too high, the acid solution will corrode the surface of the substrate, and if the temperature is too low, the iron oxide scale cannot be fully removed. The present invention sets the pickling temperature to 85-90°C.
[0051] Cold rolling reduction rate: The greater the degree of deformation during cold rolling, the higher the internal stress, the more unstable the steel is inside, and the easier it is for the structure to recrystallize. In order to suppress recrystallization during the soaking process and retain more than 85% of the rolled structure, the cold rolling reduction rate is controlled at 50-70%.
[0052] Annealing temperature: In order to ensure that a large amount of deformed non-recrystallized tissue is still retained in the structure after hot-dip galvanizing to ensure high strength, the temperature must be below the recrystallization temperature during the heating process before hot-dip galvanizing. Too high an annealing temperature will cause a large amount of deformed tissue to recrystallize after cold rolling, thereby greatly reducing the strength of the material. Too low an annealing temperature will cause the structure after annealing to still be completely rolled structure, with too high strength and too low elongation. Therefore, the present invention controls the temperature at 560-580°C. When the temperature is lower than 560°C, the material is completely rolled structure and the elongation is too low. When the temperature is higher than 580°C, the material partially recrystallizes and the strength decreases significantly.
[0053] Holding time: At a certain annealing temperature, the longer the holding time, the greater the degree of recovery and recrystallization of the deformed structure, and the strength of the material will decrease. In order to keep the deformed non-recrystallized structure above 85%, the annealing time is controlled at 40 to 80 seconds. The higher the annealing temperature, the shorter the holding time, and the relationship between the two is t = 1220-2 × T; where T is the annealing temperature, unit ℃; t is the holding time, unit s.
[0054] Radiant tube heating: Since the properties of steel change dramatically with the change of temperature near the recrystallization temperature, the temperature must be strictly controlled within the set temperature range. Therefore, the annealing process uses radiant tube heating instead of open flame heating.
[0055] Hydrogen concentration in the furnace: In the present invention, low-temperature uniform heating is adopted. Compared with high-temperature uniform heating, the reducing effect of hydrogen is weaker. Therefore, in order to improve the reducing effect of hydrogen, the concentration of hydrogen needs to be increased. In the present invention, the hydrogen concentration is controlled to be not less than 15%.
[0056] Zinc-magnesium-aluminum plating bath temperature: The Al content of the present invention is high, and the melting point of the plating bath is high. Therefore, the plating bath temperature is high, and the zinc ash and zinc slag will increase. At the same time, the corrosion of the plating bath on the substrate is also strengthened, which is not conducive to the surface quality and adhesion of the plated product. Therefore, the plating bath temperature of the present invention is controlled to be 30-40°C higher than the melting point of the plating bath.
[0057] Compared with the prior art, the present invention has the following beneficial effects:
[0058] The present invention retains a large amount of deformed non-recrystallized structure in the substrate through low-temperature annealing without adding strengthening elements such as Nb and Ti, thereby ensuring high strength. Then, by adjusting the chemical composition of the zinc-aluminum-magnesium plating solution and optimizing the manufacturing process, the problems of plating leakage and poor coating adhesion caused by residual iron oxide scale caused by low-temperature annealing are solved, and finally high strength and high corrosion resistance of the steel plate are achieved. BRIEF DESCRIPTION OF THE DRAWINGS
[0059] Figure 1 This is the microstructure diagram of the substrate after annealing in Example 1.
[0060] Figure 2 This is the microstructure diagram of the substrate after annealing in comparative example 2.
[0061] Figure 3 This is the microstructure diagram of the substrate after annealing in comparative example 3.
[0062] Figure 4 This is the microstructure diagram of the coating layer of Example 1. DETAILED DESCRIPTION
[0063] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.
[0064] A high-corrosion-resistant and high-strength zinc-aluminum-magnesium coated steel plate comprises a substrate and a zinc-aluminum-magnesium coating formed by a hot-dip zinc-aluminum-magnesium coating solution; wherein the chemical composition and mass percentage of the substrate are: C: 0.02-0.07%, Si: 0.02-0.10%, Mn: 0.7-0.9%, Als: 0.02-0.07%, P≤0.025%, S≤0.02%, and the balance is Fe and other inevitable impurities; the chemical composition and mass percentage of the zinc-aluminum-magnesium coating solution are: Al: 30.0-45.0%, Mg: 5.0-8.0%, Si: 0.5-1.2%, and the balance is Zn and other inevitable impurities.
[0065] The method for manufacturing the above-mentioned high corrosion-resistant and high-strength zinc-aluminum-magnesium coated steel plate comprises the following steps:
[0066] 1) Smelting and continuous casting
[0067] Continuous casting after smelting according to the composition of the substrate;
[0068] 2) Hot rolling
[0069] The continuously cast slab is heated to a furnace temperature of 1150-1190°C; then hot rolled to a final rolling temperature of 800-840°C; the hot rolled strip is cooled to 520-570°C and coiled;
[0070] 3) Pickling and cold rolling
[0071] The obtained hot-rolled coil is pickled at an acid solution temperature of 85 to 90° C.; and then cold-rolled at a total reduction rate of 50 to 70% to obtain a substrate;
[0072] 4) Hot dip galvanizing
[0073] The substrate is heated to the annealing temperature by a radiation tube in an annealing furnace, the heating rate is 5-30K / s, the annealing temperature is 570-590°C, the holding time is 40-80s, and the annealing temperature and the holding time satisfy the formula: t=1220-2×T; wherein T is the annealing temperature, in °C; t is the holding time, in seconds; the hydrogen concentration in the annealing furnace is ≥15%, and the dew point is ≤-40°C;
[0074] The annealed substrate is placed in a zinc pot for hot-dip zinc-magnesium-aluminum plating solution. The plate temperature of the substrate when entering the zinc pot is 5-10°C higher than the temperature of the zinc-magnesium-aluminum plating solution, and the temperature of the zinc-magnesium-aluminum plating solution is 30-40°C higher than its melting point. The substrate is cooled after being taken out of the pot, and the average cooling rate is greater than 35K / s to obtain a high corrosion-resistant and high-strength zinc-aluminum-magnesium coated steel plate.
[0075] The following examples are used to manufacture high-corrosion-resistant and high-strength zinc-aluminum-magnesium coated steel sheets according to the above-mentioned composition and method, and comparative examples are also introduced for comparison. The specific parameters are shown in Tables 1 to 4. The properties of the steel sheets obtained in the examples and comparative examples are tested, including yield strength, tensile strength, elongation, CCT plane red rust resistance cycle and 1T bending test; in order to better compare the effect, the coating thickness of the test steel sheets is 100g / m on one side. 2 The results are shown in Table 5. The test of the red rust resistance cycle of the CCT plane refers to the standard JASO M609-91, and the specific test conditions are: one cycle is 8 hours; 2 hours of salt spray, using 5% NaCl solution, temperature 35°C; then 4 hours of drying at 60°C, relative humidity 20-30%; then 2 hours of humidification, temperature 50°C, relative humidity 95%; the above steps are repeated until red rust appears; the cycle from the start of the experiment to the appearance of red rust is taken as the CCT plane red rust resistance cycle.
[0076] Table 1 Chemical composition of substrate
[0077] Substrate No. C(%) Si(%) Mn(%) Als(%) P(%) S(%) 1 0.04 0.07 0.7 0.020 0.024 0.012 2 0.02 0.10 0.9 0.043 0.016 0.009 3 0.07 0.05 0.7 0.068 0.012 0.011 4 0.05 0.02 0.8 0.037 0.019 0.007
[0078] Table 2 Chemical composition and melting point of zinc-magnesium-aluminum plating solution
[0079] Bath No. Al(%) Mg(%) Si(%) Plating solution melting point (℃) 1 30.1 5.0 0.51 507 2 35.4 7.7 0.60 509 3 36.7 6.3 0.69 518 4 40.5 7.1 0.92 523 5 45.0 7.9 1.20 529 <![CDATA[ 6 ]]> <![CDATA[ 22.4 ]]> 5.1 0.52 483 <![CDATA[ 7 ]]> 30.0 5.2 <![CDATA[ 0.32 ]]> 506
[0080] Table 3 Manufacturing process parameters (I)
[0081]
[0082]
[0083] Table 4 Manufacturing process parameters (II)
[0084]
[0085] Table 5 Specific conditions and performance results of each embodiment and comparative example
[0086]
[0087]
[0088] Note: √: Adhesion is qualified; ×: Adhesion is unqualified, and there is dezincification.
[0089] It can be seen from Table 5 that the steel plates obtained in various embodiments of the present invention all exhibit high strength and high corrosion resistance, and the coating has excellent adhesion, and the coating does not crack or fall off during 1T bending. Figure 1 This is a microstructure diagram of the substrate after annealing in Example 1. It can be seen from the figure that the microstructure of the substrate after annealing includes ferrite and carbide, and the area of the deformed non-recrystallized microstructure accounts for 93%. Figure 2 This is the microstructure diagram of the substrate after annealing in Comparative Example 2. When the annealing temperature is too low, the microstructure does not recover and recrystallize at all, and the strength is very high, but the elongation is less than 4%, which is not conducive to simple processing. Figure 3 The microstructure of the substrate after annealing in Comparative Example 3 shows that when the annealing temperature is too high, most of the rolled microstructure undergoes recrystallization, resulting in a significant decrease in strength. According to Comparative Examples 1 and 4, when the reduction ratio is too large or the annealing time is too long, the rolled microstructure undergoes partial recrystallization, resulting in a decrease in strength.
[0090] The zinc-aluminum-magnesium coating formed in each embodiment of the present invention includes a coating layer and an interface layer between the substrate and the coating layer; Figure 4 This is the microstructure diagram of the coating layer of Example 1, which includes primary (Al) phase, MgZn2 phase, multi-element eutectic Al / Zn / MgZn2 structure, and Mg2Si phase; and the interface layer is a dense Al-Fe compound containing a small amount of Si. Comparative Example 5 shows that when the Al content of the plating solution is low, for the steel plate after low-temperature annealing, the reaction between the plating solution and the steel plate is weak, resulting in defects such as exposed plating and poor adhesion, resulting in failure of the bending test. Comparative Example 6 shows that when the Si content of the plating solution is too low, Si cannot effectively inhibit the growth of the Al-Fe interface layer, the plating solution will seriously corrode the steel base, and the interface layer is too thick, resulting in failure of the bending test.
[0091] Comparative Examples 7 to 9 show that when the billet out of the furnace temperature is too high, or the final rolling temperature is too high, or the coiling temperature is too high, a thick iron oxide scale is generated on the surface of the substrate, which cannot be completely removed in the subsequent process, reducing the corrosion resistance and adhesion of the coating after hot-dip. Comparative Example 10 shows that when the pickling temperature is too low, the iron oxide scale cannot be effectively removed, reducing the corrosion resistance and adhesion of the coating. Comparative Example 11 shows that when the hydrogen concentration is too low, the reduction effect of hydrogen is weak, and an oxide layer remains on the surface of the strip, affecting the wetting of the plating solution on the substrate, reducing the corrosion resistance and adhesion of the coating. Comparative Example 12 shows that when the dew point in the annealing furnace is too high, the surface of the strip is locally oxidized, affecting the wetting of the plating solution on the substrate, reducing the corrosion resistance and adhesion of the coating. Comparative Example 13 shows that when the plating solution temperature is too high, the zinc ash and zinc slag increase significantly, reducing the adhesion of the coating.
[0092] The above embodiments are merely examples for clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above descriptions. It is not necessary and impossible to list all the implementation methods here, and the obvious changes or modifications derived therefrom are still within the protection scope of the invention.
Claims
1. A high corrosion resistance and high strength zinc-aluminum-magnesium coated steel plate, characterized in that: The invention comprises a zinc-aluminum-magnesium coating formed by a substrate and a hot-dip zinc-aluminum-magnesium plating solution; the chemical composition and mass percentage of the substrate are as follows: C: 0.02-0.07%, Si: 0.02-0.10%, Mn: 0.7-0.9%, Als: 0.02-0.07%, P≤0.025%, S≤0.02%, and the balance is Fe and other inevitable impurities; the chemical composition and mass percentage of the zinc-aluminum-magnesium plating solution are as follows: Al: 30.0-45.0%, Mg: 5.0-8.0%, Si: 0.5-1.2%, and the balance is Zn and other inevitable impurities.
2. The high corrosion resistant and high strength zinc-aluminum-magnesium coated steel sheet according to claim 1, characterized in that: The high corrosion-resistant and high-strength zinc-aluminum-magnesium coated steel plate has a yield strength of ≥550MPa, a tensile strength of ≥550MPa, and an elongation of ≥4%.
3. The method for manufacturing a high corrosion resistant and high strength zinc-aluminum-magnesium coated steel sheet according to claim 1 or 2, characterized in that: The following steps are involved: 1) Smelting and continuous casting Continuous casting after smelting according to the composition of the substrate; 2) Hot rolling The continuously cast slab is heated to a furnace temperature of 1150-1190°C; then hot rolled to a final rolling temperature of 800-840°C; the hot rolled strip is cooled to 520-570°C and coiled; 3) Pickling and cold rolling The obtained hot-rolled coil is pickled and then cold-rolled with a total reduction ratio of 50 to 70% to obtain a substrate; 4) Hot dip galvanizing The substrate is heated to an annealing temperature in an annealing furnace and kept warm, the annealing temperature is 570-590°C, and the holding time is 40-80s; the annealed substrate is put into a zinc pot for hot-dip zinc-magnesium-aluminum plating solution, and is cooled after being taken out of the pot to obtain a high corrosion-resistant and high-strength zinc-aluminum-magnesium coated steel plate.
4. The method for manufacturing a high corrosion resistant and high strength zinc-aluminum-magnesium coated steel sheet according to claim 3, characterized in that: The annealing temperature and the holding time satisfy the formula: t=1220-2×T; wherein T is the annealing temperature, in units of °C; and t is the holding time, in units of seconds.
5. The method for manufacturing a high corrosion resistant and high strength zinc-aluminum-magnesium coated steel sheet according to claim 3, characterized in that: The annealing furnace is heated by a radiation tube, the heating rate is 5-30K / s, the hydrogen concentration in the annealing furnace is ≥15%, and the dew point is ≤-40°C.
6. The method for manufacturing a high corrosion resistant and high strength zinc-aluminum-magnesium coated steel sheet according to claim 3, characterized in that: The thickness of the substrate is 0.40-2.5 mm; the structure of the substrate after annealing includes ferrite and carbide, wherein the area of the deformed non-recrystallized structure accounts for 85-96%.
7. The method for manufacturing a high corrosion resistant and high strength zinc-aluminum-magnesium coated steel sheet according to claim 3, characterized in that: The plate temperature of the substrate when entering the zinc pot is 5-10°C higher than the temperature of the zinc-magnesium-aluminum plating solution, the temperature of the zinc-magnesium-aluminum plating solution is 30-40°C higher than its melting point, and the average cooling rate after leaving the pot is greater than 35K / s.
8. The method for manufacturing a high corrosion resistant and high strength zinc-aluminum-magnesium coated steel sheet according to claim 3, characterized in that: The zinc-aluminum-magnesium coating includes a coating layer and an interface layer between the substrate and the coating layer; the structure of the coating layer includes a primary crystal (Al) phase, a MgZn2 phase, a multi-electrotectic Al / Zn / MgZn2 structure, and a Mg2Si phase; the interface layer is a dense Al-Fe compound containing a small amount of Si.
9. The method for manufacturing a high corrosion resistant and high strength zinc-aluminum-magnesium coated steel sheet according to claim 3, characterized in that: The acid solution temperature of the pickling is 85-90°C.
Citation Information
Patent Citations
Hot-dipped aluminum-zinc or zinc-aluminum-magnesium complex-phase steel with yield strength of 550MPa and manufacturing method thereof
CN115161542A
High-corrosion-resistance hot-dip galvanized aluminum magnesium high-strength steel and manufacturing method thereof
CN117327992A
High-strength hot-dip galvanized steel sheet excellent in metal-plating property, and producing method thereof
JP2008038168A
Hot-dip galvanized steel sheet having tensile strength of 980 mpa or more and excellent in formability and production method of the same
JP2013076148A